Application of the Stad Learning Model to Improve Student Learning Outcomes in Grade IV SD Negeri 0701 Rattan Sogo - Arman Saddam Daulay (Indonesian Journal of Basic Education, 2022)
By applying the STAD type cooperative learning model assisted by video media, research was carried out to improve the learning outcomes of fourth grade students of SD Negeri 0701 Rotan Sogo whith material. This research is motivated by the fact that most students are less active and less interested in learning style material due to the lack of diversity in teacher performance during the learning process. The purpose of this study was to improve student learning outcomes at SD Negeri 0701 Rotan Sogo Class 4 Gaya. This type of research is classroom action research. The research subjects were all fourth grade students of SD Negeri 0701 Rotan Sogo, with a total of 34 students enrolled in the 2022/2023 academic year consisting of 17 male students and 17 female students. Data was collected through tests, observations, and interviews. The results showed that the use of the STAD type cooperative learning model assisted by video media could improve student learning outcomes for the style material. Classical learning completeness level data increased from 68% (pre-test) to 82% (period I) to 94% (period II). Observation of teacher activity increased from an average of 7.4 (period I) to 9.3 (period II). Observation of student activity increased from an average of 7.6 (cycle I) to 9.3 (cycle II)